Pengaruh Influencer Marketing, Eletronic Word of Mouth dan Brand Image terhadap Keputusan Pembelian pada Konsumen Produk Kecantikan Facetology Generasi Z Kota Malang - Putri, Restu Cahyani; Wahono, Budi; Dianawati, Eris (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study is to examine how Generation Z in Malang City makes decisions on Facetology product purchases in relation to Influencer Marketing, Electronic Word of Mouth (eWOM), and Brand Image. With an explanatory research approach, a quantitative research methodology is employed.  Because the population size was unknown, the sample strategy used purposive sampling and included 96 late Gen Z respondents, as determined by Lemeshow's algorithm.  A questionnaire was used to gather the data, and multiple linear regression was used for analysis.  The findings show that brand image, eWOM, and influencer marketing have a big impact on purchase decisions. Keywords: Influencer Marketing, eWOM, Brand Image, Purchase Decision